Is There Space for Our Stories? An Examination of North American and Western European Gay, Bi, and Other Men Who Have Sex with Men's Non-consensual Sexual Experiences. Issue 8 (12th October 2020) - McKie, Raymond M.; Skakoon-Sparling, Shayna; Levere, Drake; Sezlik, Sage; Humphreys, Terry P.
ABSTRACT: The present study examined the understanding and behaviors relating to sexual consent among gay, bisexual, and other men who have sex with men (GBM) internationally. Qualitative responses were collected from 350 men ranging from 18 to 73 years of age ( M = 33.37) across Canada, the United States, and Western Europe. The results of a thematic analysis indicated that participants presented challenges with negotiating sexual consent. Themes were identified from the analysis detailing participants' perceptions and interactions prior to a sexual encounter (pre), during a sexual encounter (during), and after a sexual experience (post). Subthemes addressed a variety of issues GBM may face when engaging in sexual consent negotiations (e.g., sex-role positioning, power dynamics, sexual scripts among GBM, and additional sexual settings). These findings suggest that GBM face unique sexual consent challenges prior to, during, and in response to sexual encounters. Implications for demographic-specific resources and interventions are discussed further.